PHYSICAL COMPOSITION OF CARCASSES IN BROILERS THAT GIVEN MANGOSTEEN PEEL EXTRACT (Garcinia mangostana L.) THROUGH DRINKING WATER - A. P., Haloho; Astawa, I P.A.; Ariana, I N. T. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the effect of mangosteen peel extract with different concentrations through drinking water on the physical composition of broiler carcasses aged 35 days. The research was conducted in Banjar Jambe Baleran, Dajan Pekan Village, Tabanan for 5 weeks. The design used was a completely randomized design (CRD) consisting of 4 treatments and 4 replicates, so there were 16 experimental units. Each experimental unit used 5 broilers aged 1 days and a total of 80 broilers were used. The treatments given were P0: 0% mangosteen peel extract, P1: 1% mangosteen peel extract, P2: 2% mangosteen peel extract and P3: 3% mangosteen peel extract. The variables observed were carcass weight, carcass percentage, meat, bone and subcutaneous fat including skin. The results showed that broilers given mangosteen peel extract as much as 1% - 3% (P1, P2 and P3) had carcass weight, carcass percentage, meat percentage, bone percentage and subcutaneous fat percentage including skin that was not significantly different (P>0.05) from the control (P0). Based on the results of this study it can be concluded that the provision of mangosteen extract through drinking water as much as 1% - 3% has no effect on the Physical Composition of broiler carcasses aged 35 days.